PO238 Transverse sinus stenting in iih: 27 cases in wessex neurological centre. (1st December 2017) - Osman, Chinar; Wang, Difei; Lovett, Joanna; Pinto, Ashwin; Macdonald, Jason
Abstract : Background: Transverse sinus stenosis is commonly seen in patients with idiopathic intracranial hypertension (IIH). Although the aetiology remains controversial, limited studies of treating IIH with transverse venous sinus stenting (VSS) have shown promising results. Materials and Method: We studied the first 27 consecutive patients prospectively with IIH who underwent VSS. Eligibility criteria were: medically refractory IIH, papillodema, significantly raised intracranial venous sinus pressures above the stenosis and a significant pressure gradient across the stenosis. Results: Twenty-seven patients with a mean age of 32 years and a mean BMI of 36 Kg/m2 pre-procedure were included and followed up for a median of 20 (range 5–45) months. The mean pressure gradient across the transverse sinus was 19.2 mmHg. Twenty-five out of the twenty-seven patients successfully underwent VSS. Stent placement was unsuccessful in the remaining two patients (7%). Papillodema resolved in 21 cases; headache resolved in 14 cases and improved in 8 cases. In summary, 22 out of 25 (88%) patients stented had resolution of their symptoms and signs of raised intracranial pressure, giving an overall success rate of 22/27 (81%). Conclusion: Our study suggests that VSS is effective at treating refractory IIH and offers an alternative to CSF shunting.